To solve this question, we must break down the question into different scenarios.
The speed expression for the first rider is:
![\begin{gathered} s=(d)/(t) \\ \text{let us make the distance the first rider covers as y.} \\ d=y\text{ miles} \\ t=3\text{ hours.} \\ s_1=(y)/(3) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/zjlsq5kvm3u7jdvuh9j325ane4rlf51wx4.png)
The speed expression for the second cyclist:
![\begin{gathered} s=(d)/(t) \\ the\text{ first rider covered a distance of y miles, the remaining distance } \\ \text{left for the second cyclist to cover is:} \\ (108-y)\text{miles at the same time of 3 hours.} \\ s_2=(108-y)/(3) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/h2wt3k6so382tk3ztjx4yji5292y0zo5wd.png)
Since one cyclist cycles 3 times as fast as the other:
It is expressed thus:
![\begin{gathered} s_1=3* s_2 \\ s_1=3s_2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/b3uh6bjs17wplvjciq37sgfj2afwlaekdm.png)
Now substitute the values for the speed expression into the expression above, we will have:
![(y)/(3)=3*((108-y)/(3))](https://img.qammunity.org/2023/formulas/mathematics/college/un1b3nsq6fbxelwjma0wdvpla0ai8nf0j1.png)
By solving the above expression, we will get the value of y (part of the distance travelled) and we can get the speed of the faster cyclist.
![\begin{gathered} (y)/(3)=(324-3y)/(3) \\ y=324-3y \\ y+3y=324 \\ \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/t05nu8jdqknp06yjo4jbvxg8n68twwpghi.png)
![\begin{gathered} 4y=324 \\ y=(324)/(4) \\ y=81\text{ miles.} \\ \\ So\text{ the speed of the faster cyclist will be:} \\ _{}=(y)/(3) \\ =\frac{81\text{ miles}}{3\text{ hours}} \\ =27mi\text{/h} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/nf1pwmlia8r9skjkrpxxh0tsvh8ikvn6sf.png)
The speed of the faster cyclist is 27 mi/h.